The Little shop of horrors - Corman, Roger, 1926-; Griffith, Charles B.; Haze, Jonathan; Filmgroup (1959-1962) (United States : Filmgroup, 1960)
Symour is an employee of a florist who develops a new species by crossing groups of carnivorous plants. At his creation, he names her Audrey Jr. in honor of his partner, with whom he is deeply in love. He will soon discover that the plant acquires unusual eating habits, having to feed it with its own blood. But his appetite will become voracious, so he will be forced to murder to satisfy her, especially since his size will become the main attraction of the store.--
Jonathan Haze, Jackie Joseph, Mel Welles.
Photographer, Archie Dalzell ; film editor, Marshall Nellan, Jr. ; music by Fred Katz.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: Motion pictures; Comedy films; Monster films; Feature films; Streaming video